Evolutionary Co-Option of Floral Meristem Identity Genes for Patterning of the Flower-Like Asteraceae Inflorescence. Issue 1 (5th July 2016) - Zhao, Yafei; Zhang, Teng; Broholm, Suvi K.; Tähtiharju, Sari; Mouhu, Katriina; Albert, Victor A.; Teeri, Teemu H.; Elomaa, Paula
Abstract : Highly conserved genes that regulate the identity of single flowers in conventional plant models regulate the unique inflorescence architecture of the evolutionarily successful Asteraceae plant family. Abstract: The evolutionary success of Asteraceae, the largest family of flowering plants, has been attributed to the unique inflorescence architecture of the family, which superficially resembles an individual flower. Here, we show that Asteraceae inflorescences (flower heads, or capitula) resemble solitary flowers not only morphologically but also at the molecular level. By conducting functional analyses for orthologs of the flower meristem identity genes LEAFY ( LFY ) and UNUSUAL FLORAL ORGANS ( UFO ) in Gerbera hybrida, we show that GhUFO is the master regulator of flower meristem identity, while GhLFY has evolved a novel, homeotic function during the evolution of head-like inflorescences. Resembling LFY expression in a single flower meristem, uniform expression of GhLFY in the inflorescence meristem defines the capitulum as a determinate structure that can assume floral fate upon ectopic GhUFO expression. We also show that GhLFY uniquely regulates the ontogeny of outer, expanded ray flowers but not inner, compact disc flowers, indicating that the distinction of different flower types in Asteraceae is connected with their independent evolutionary origins from separate branching systems.